Teachers' knowledge on ADHD, opinions on ADHD stimulant medication and the teaching of students with ADHD - Choo, Chian Hou, 1987-; Yeo, Kee Jiar, supervisor; Fakulti Pendidikan (2013)
Thesis (Sarjana Pendidikan (Psikologi Pendidikan)) - Universiti Teknologi Malaysia, 2013